CogniStim: Physical and cognitive real-time stimulator using inertial sensors in a virtual reality environment for elderly people - Gomes, Pedro Eugénio Barbosa (2018)
Dissertação de Mestrado Integrado em Engenharia Electrotécnica e de Computadores apresentada à Faculdade de Ciências e Tecnologia